Dynasties and female political leaders in Asia gender, power and pedigree - Derichs, Claudia; Thompson, Mark R. 1960- (olitikwissenschaftliche Perspektiven, 2013)
This book is the first comprehensive academic effort to examine the phenomenon of top female political leaders in Asia. It portrays prime ministers, presidents, and opposition leaders, but it is not a conventional biographical volume. Rather, it analyzes female politicians by means of case studies that are based on a common theoretical framework. The case studies were conducted over three years of field research, which included interviews with the female leaders themselves and members of their inner circle. Each chapter explores the similarities, but also points to the distinctiveness of each female leader, arising from political and social systems, cultural and religious conditions, and economic parameters